In vitro Antioxidant, Enzyme Inhibitory and Antimicrobial Evaluation of Sideritis caesarea H. Duman, Aytac & Baser Extracts - Gunbatan, Tugba; Gurbuz, Ilhan; Karaca, Nursenem; Demirci, Fatih (Sage Publications Inc, 2023)
Sideritis caesarea H. Duman, Aytac & Baser of the family Lamiaceae is an endemic plant with different ethnobotanical uses in Anatolia. In this present study, the antioxidant and biological activity potential of different S caesarea extracts and purified compounds were evaluated in vitro using DPPH center dot, CUPRAC, and ABTS center dot methods. In addition, their urease and chymotrypsin enzyme inhibitory activities, antimicrobial potential, and total phenol and flavonoid contents were determined. The experimental results showed that the two isolated flavonoids {4 '-O-methylhypolaetin-7-O-[6 '''-O-acetyl-beta-D-allopyranosyl-(1 -> 2)]-6 ''-O-acetyl-beta-D-glucopyranoside, and isoscutellarein-7-O-[6 '''-O-acetyl-beta-D-allopyranosyl-(1 -> 2)]-6 ''-O-acetyl-beta-D-glucopyranoside}, as well as their fractions, except the n-hexane and water residue, showed remarkable antioxidant activity. Interestingly, the ethyl acetate and water residue fractions inhibited the urease enzyme activity by 49.6% and 49.1%, respectively; while the n-hexane and dichloromethane fractions attracted attention with their relative high chymotrypsin inhibitory activity of 85.8%, and 82.4%, respectively. When evaluated for their in vitro antimicrobial potential, including Helicobacter pylori, only Bacillus subtilis was susceptible to the n-butanol fraction at 1 mg/mL, while all of the studied samples showed activity against the human pathogenic yeast Candida albicans with the range of 0.25 to 1 mg/mL minimum inhibitory concentrations. The initial antioxidant activity, enzyme inhibitions, and antimicrobial results of S caesarea extracts and compounds suggest the further potential for in vivo evaluations.
Keywords: Sideritis caesarea; folk medicine; flavonoids; antioxidant activity; urease; chymotrypsin